Worm - Bailey, Jill. (Des Plaines, Ill. : Heinemann Library, 1998)
A simple introduction to the physical characteristics, diet, life cycle, predators, habitat, and lifespan of worms.
Includes bibliographical references (p. 32) and index.
Science and Children (N.S.T.A.).
L.A. Recommended Foreign Language.
2.8
K-3
Keywords: Worms -- Juvenile literature; Worms; Worms; Worms